The influence of sugar-phosphate backbone on the stacking interaction in B-DNA helix formation - Mittal, Sumit; Sathyamurthy, N. (Indian Academy of Sciences, 2015)
The influence of sugar-phosphate backbone on the stacking interaction in the adenine...thymine base-pair dimer (A...T)2 has been studied using the density functional theoretic method and the dispersion-corrected density functional BLYP-D3 and the triple-zeta quality basis set def2-TZVP. In the absence of the sugar-phosphate backbone, several stacked conform-ers were obtained with a small difference in their stabilization energy values (-20 to -25 kcal/mol). However, the presence of the sugar-phosphate back-bone limits the movement of the two A...T units, and yet the stacking interaction remains significant (-19.4 kcal/mol). Despite the constraints imposed by the backbone, the dimer (A...T)2 is found to retain its favourable geometry. The influence of sodium ions on the geometry and the interaction energy is found to be negligible.
Only IISERM authors are available in the record.
Keywords: B-DNA helix formation; BLYP-D3; Stack-ing interaction; Sugar-phosphate backbone